2007
DOI: 10.1162/jocn.2007.19.5.721
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation in a Finger-tapping Task Separates Motor from Timing Mechanisms and Induces Frequency Doubling

Abstract: We study the interplay between motor programs and their timing in the brain by using precise pulses of transcranial magnetic stimulation (TMS) applied to the primary motor cortex. The movement of the finger performing a tapping task is periodically perturbed in synchronization with a metronome. TMS perturbation can profoundly affect both the finger trajectory and its kinematics, but the tapping accuracy itself is surprisingly not affected. The motion of the finger during the TMS perturbation can be categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Although the present data suggest that neural processing is most efficient during continuation when representations can be used that have established the timed motor behaviour, it is also noted that temporal information can be easily transferred between effector combinations, as evident from the behavioural data. The findings are further supportive of the premise that timing and motor functions are separately controlled in tapping tasks (Levit‐Binnun et al ., 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Although the present data suggest that neural processing is most efficient during continuation when representations can be used that have established the timed motor behaviour, it is also noted that temporal information can be easily transferred between effector combinations, as evident from the behavioural data. The findings are further supportive of the premise that timing and motor functions are separately controlled in tapping tasks (Levit‐Binnun et al ., 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Thus many authors have demonstrated a linear increase in the variance of the central timer as a function of interval, while the variance of the motor implementation is constant across the produce intervals (Balasubramaniam et al 2004;Ivry and Keele 1989;Wing 1980; see Wing 2002 for a review). In line with these observations, a recent study showed that transcranial magnetic stimulation in the motor cortex applied synchronously with the sensory metronome induced complex finger trajectories, but did not had an effect on the temporal performance on human subjects performing a synchronization tapping task (Levit-Binnun et al 2007). Due to the kinematic analysis of the velocity of the tapping behavior, in the present paper we were able to directly quantify the duration of the pause and the motor execution, and our results demonstrate for the first time that only the pause follows the scalar property of interval timing (Gibbon et al 1997).…”
Section: Discussionmentioning
confidence: 66%
“…Our results point to the potential for stimulating the motor cortex to significantly influence complex motor performance. Previous research has explored the effects of non-invasive brain stimulation on basic motor behaviors associated with M1, such as speed, accuracy and force of movement (Muellbacher et al, 2000;Jäncke et al, 2004;Levit-Binnun et al, 2007). Post hoc analyses in the present study revealed that the significant effects of stimulation were driven primarily by changes in the speed of keystrokes; this suggests that influencing processes that are probably mediated by motor cortex, such as accuracy and speed, can have a significant impact at the level of a complex behavior.…”
Section: Discussionmentioning
confidence: 99%